Economic recovery programme, 1996-1998 (Abuja, Nigeria : The national Economic Intelligence Committee, 1996)
This is a report of a fourteen member committee that was set up to analyze the annual budget of the Federal Government and extract from it all economic measures requiring enforcement; work out details on the method of enforcing implementation of the annual budget; analyze the monetary guidelines issued by the Central Bank of Nigeria and monitor the implementation of all the measures enumerated therein.
Includes bibliographical references
hza 14/02/2019
Loans
Keywords: Budget (public); Nigeria